Compound‐Specific Stable Isotope Analysis Reveals Population‐Specific Differences in Chinook Salmon Trophic Level and Basal Resource Use in the Northeast Pacific - Jacob E. Lerner; Brian P. V. Hunt (Fisheries Oceanography, 2026)
Chinook salmon exhibit far‐flung and disparate population‐specific marine migrations that have made it difficult to assess their trophic ecology. In this study, we collected returning and resident subadult Fraser River Chinook salmon in 2018 and 2019 from population groups with different known run‐timings (spring, summer, and fall) and marine distributions relative to the Fraser River (local/south, north, offshore) and processed them for carbon and nitrogen CSIA‐AA. We investigated population‐specific differences in trophic level using δ 15 N AA , and used δ 13 C AA with published taxon‐specific fingerprints of phytoplankton groups to investigate differences in the primary producer base that underpinned the food web they experienced. The south/local Fraser Fall 4 1 population exhibited distinct δ 13 C AA values from the north and offshore Summer 4 1 , Spring 5 2 , and Summer 5 2 populations, likely due to their different geographic distributions and corresponding differences in primary producer communities. Chinook salmon trophic level was variable, with evidence for more omnivory and lower trophic levels in the southern distributing populations (TL = 3.7 ± 0.2) relative to the northern ones (TL = 3.9 ± 0.1), although there was interannual variability in the trophic level of the southern distributing population. This analysis builds on previous investigations of Chinook salmon marine ecology, linking distribution to basal food web resources to trophic level, and highlights the importance of population‐specific marine distributions in structuring Chinook salmon trophic ecology. Knowledge of their food web ecology is necessary to understand how this species is and will respond to changing climate and ocean conditions and support management and conservation efforts.